The implementation of sinusoidal PWM on single phase 5-level cascaded H-bridge multilevel inverter - Yaakub, Muhamad Faizal (2013)
In the new millennium era of technology, modern industrial devices are mostly based on electronic devices that are very sensitive to harmonics. The needs for a free-harmonics and high rating power source is extremely increased in the past few years to meet the requirement from the industries. An inverter which converts DC power to AC power is one of the power electronic devices that have been in the researchers’ radar for further improvement to generate a clean power source. An inverter can be broadly classified into single level inverter and multilevel inverter. A multilevel inverter as compared to a single level inverter has advantages like minimum harmonics distortion and higher power output. An implementation of cascaded h-bridge topology and a sinusoidal pulsewidth modulation, synthesize a higher quality output power especially with multilevel configuration.